Two Cases of Hypokalaemic Periodic Paralysis due to Conn’s Syndrome (Bangladesh Critical Care Journal, 2023)
Aldosterone producing adenoma, also known as Conn’s syndrome, is the most common secondary form of hypertension. Conn’s syndrome is characterized by hypertension with increased aldosterone, low renin, hypernatremia and hypokalaemia. Clinical manifestations include hypertension in young or resistant hypertension, generalized weakness and fatigue. Here we report two cases presenting with hypokalaemic periodic paralysis and ultimately diagnosed as primary hyperaldosteronism due to Conn’s syndrome.Bangladesh Crit Care J September 2023; 11 (2): 130-132